ANALISIS KINERJA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN JEPARA DALAM UPAYA PENGEMBANGAN OBYEK WISATA KARIMUNJAWA - Asilya, Sella Rizky; Widowati, Nina; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Tourism is currently the highest foreign exchange contributor sector. Indonesia is trying to maximize tourism development. Therefore, the Department of Tourism and Culture of Jepara as a tourism activist in Jepara is increasing tourism in Jepara. But there are still a number of problems that have not maximum. This study to analyze organizational performance and performance supporting factors. The assessment conducted with research the performance indicators that writer is use which are performance indicators, Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. While the supporting factors of work were assessed from human resources and infrastructure. This research uses descriptive qualitative research method by describing the findings in the field and interview. Based on the research, the performance Department of Tourism and Culture of Jepara was not optimal. It is proven by the problems that exist in all performance indicators and supporting factors that are still not optimal, so that the organization achieves performance that is not optimal and needs improvement.